Altered airway ciliary orientation in patients with X-linked retinitis pigmentosa. Issue 9 (20th May 2019) - McCray, Gabrielle; Griffin, Paul; Martinello, Paul; de Iongh, Robb; Ruddle, Jonathan; Robinson, Phil
Abstract : Previous reports suggested links between respiratory ciliary dysfunction and primary ciliopathies such as X-linked retinitis pigmentosa (XLRP). To investigate if patients with XLRP have abnormal airway ciliary structure or function, we assessed respiratory ciliary beat pattern and ultrastructure, including ciliary orientation, in 12 patients with XLRP without respiratory disease and 10 control subjects. Patients with XLRP had normal ciliary ultrastructure but significantly (p=0.004) increased mean ciliary deviation (33.8°±9.4°) compared with normal subjects (14.8°±5.4°). Altered orientation was associated with impaired ciliary beat pattern in six patients with XLRP. These findings indicate that XLRP mutations, affecting non-motile cilia of the photoreceptors in the retina, can have effects on motile cilia in the respiratory tract. The observation of disrupted ciliary orientation in patients with XLRP is suggestive of a defect in planar cell polarity.